Sequences Associated with Centromere Competency in the Human Genome - Hayden, Karen E. (American Society for Microbiology, 2013)
Centromeres, the sites of spindle attachment during mitosis and meiosis, are located in specific positions in the human genome, normally coincident with diverse subsets of alpha satellite DNA. While there is strong evidence supporting the association of some subfamilies of alpha satellite with centromere function, the basis for establishing whether a given alpha satellite sequence is or is not designated a functional centromere is unknown, and attempts to understand the role of particular sequence features in establishing centromere identity have been limited by the near identity and repetitive nature of satellite sequences. Utilizing a broadly applicable experimental approach to test sequence competency for centromere specification, we have carried out a genomic and epigenetic functional analysis of endogenous human centromere sequences available in the current human genome assembly. The data support a model in which functionally competent sequences confer an opportunity for centromere specification, integrating genomic and epigenetic signals and promoting the concept of context-dependent centromere inheritance.